Cholinergic antagonist 3-quinuclidinyl benzilate - Impact on learning and memory in Wistar rats - Misik, Jan; Vanek, Jan; Musilek, Kamil; Kassa, Jiri (Behavioural brain research, 2014)
3-Quinuclidinyl benzilate (QNB) represents a non-selective, competitive antagonist of cholinergic receptors, which has been previously used to generate cognitive deficits in animal models of neurodegenerative disorders. The aim of this study was evaluation of QNB potency for creation of cognitive impairment during the acquisition, consolidation and retrieval stages of learning and memory in rats. Male Wistar rats were subjected to a water maze task with hidden platform and a step-through passive avoidance task. The water maze test was carried out in two separate experiments focused on spatial learning (acquisition test) and long-term spatial memory (retrieval test). QNB doses (0.5, 1.0, 2.0 and 5.0 mg kg(-1)) were administered to rats intraperitoneally before training sessions (acquisition test) or before probe trial (retrieval test). A QNB dose of 2.0 mg kg(-1) was administered to rats in the passive avoidance task before training (acquisition test), immediately post-training (consolidation test) or 24h pre-retention (retrieval test). QNB significantly impaired the acquisition in the water maze at doses 0.5-5.0 mg kg(-1) as well as the acquisition of passive avoidance task. In contrast, consolidation and retrieval were not affected by QNB, indicating that QNB specifically affects the stage of acquisition.
Keywords: potkani Wistar; Dose-Response Relationship, Drug; Consolidation; pohybová aktivita; Time Factors; zvířata; Male; Passive avoidance; Avoidance Learning; Learning Disabilities; Retrieval; Quinuclidinyl Benzilate; učení vyhýbat se; neparametrická statistika; chinuklidinylbenzilát; poruchy učení; Water maze; antagonisté muskarinových receptorů; Animals; mužské pohlaví; rozpomínání; krysa rodu Rattus; Motor Activity; Rats; Rats, Wistar; Muscarinic receptors; Acquisition; časové faktory; Analysis of Variance; bludiště - učení; Disease Models, Animal; Maze Learning; Statistics, Nonparametric; modely nemocí na zvířatech; Muscarinic Antagonists; Mental Recall; analýza rozptylu; vztah mezi dávkou a účinkem léčiva